Juridical Analysis of Land Rights Ownership Arises in the Coastal Area of East Banggai District, Majene Regency - Sulaeman Sulaeman; Yasser Arafat Juanda; Asrullah Asrullah (Indonesia Prime, 2022)
This research method uses the emphyric normativ method, which combines data in the field with the results of research in the field and then analyzed in a quantitative way.This study aims to find out who is entitled to get property rights to emerging land in the East Banggae district of Majene Regency. Idealizing the policy of the local government and the National Land Agency in Majene Regency towards the legal status of land tenure arising in the coastal area of East Banggai District, Majene Regency. This research was conducted in the East Banggae sub-district with the method of collecting data, namely conducting direct interviews with the people who control the emerging land, as well as the government related.